علم الأصوات الحديث (الفونولوجيا): قضايا دراسية ونظرية وتطبيقاتها في تعليم الأصوات وتطوير مهارة الاستماع - Sumarni; Siti Shalihah (PPPBA, 2025)
ʿIlm al-Aṣwāt (phonology) is a branch of Arabic linguistics that plays a fundamental role in understanding the Arabic sound system and in developing Arabic language instruction, particularly listening skills (mahārat al-istimāʿ). With the advancement of modern linguistics, the study of ʿIlm al-Aṣwāt is no longer limited to discussions of makhārij al-ḥurūf and phonetic features, but has expanded through contemporary phonological theories such as structuralist, generative, autosegmental, optimality, and laboratory phonology. This article aims to examine the scope of modern ʿIlm al-Aṣwāt, the development of its major theories, contemporary issues in the field, and their applications in enhancing Arabic language teaching and listening skills. Employing a qualitative approach with a library research method, the study conducts a descriptive-analytical review of relevant classical and modern linguistic literature. The findings demonstrate that an understanding of modern phonetics and phonology makes a significant contribution to improving the effectiveness of Arabic language learning, particularly in strengthening learners’ listening competence and pronunciation accuracy, thereby positioning modern ʿIlm al-Aṣwāt as a strategic theoretical and pedagogical foundation in contemporary Arabic language education.